2013
DOI: 10.1371/journal.pone.0058754
|View full text |Cite
|
Sign up to set email alerts
|

Touch Interacts with Vision during Binocular Rivalry with a Tight Orientation Tuning

Abstract: Multisensory integration is a common feature of the mammalian brain that allows it to deal more efficiently with the ambiguity of sensory input by combining complementary signals from several sensory sources. Growing evidence suggests that multisensory interactions can occur as early as primary sensory cortices. Here we present incompatible visual signals (orthogonal gratings) to each eye to create visual competition between monocular inputs in primary visual cortex where binocular combination would normally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 52 publications
(74 reference statements)
10
77
3
Order By: Relevance
“…The fact that we did not find any evidence for automatic capture with tactile cues contrasts with previous studies that have suggested that touch influences visual processing in early sensory areas (Lunghi & Alais, 2013;Lunghi et al, 2010). Lunghi and Alais showed that exploration of a tactile grating produced prolonged dominance and reduced suppression of a grating of matching orientation during binocular rivalry.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The fact that we did not find any evidence for automatic capture with tactile cues contrasts with previous studies that have suggested that touch influences visual processing in early sensory areas (Lunghi & Alais, 2013;Lunghi et al, 2010). Lunghi and Alais showed that exploration of a tactile grating produced prolonged dominance and reduced suppression of a grating of matching orientation during binocular rivalry.…”
Section: Discussioncontrasting
confidence: 99%
“…Another key difference between our experiments and that of Lunghi et al (2010;Lunghi & Alais, 2013) is the level of complexity in the display. Lunghi et al and Lunghi and Alais presented only one visual item, whereas the experiments reported here used an array of visual items.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Rivalry offers a way to study the inferential nature of perception when the brain is confronted with conflicting sensory evidence (11,12). Within this context, recent studies imply that rivalry dynamics are governed by influences related to the likelihood of competing perceptual interpretations, such as motor actions (13), affective connotation (14)(15)(16), familiarity (17), and concomitant sensory input from other modalities (18)(19)(20). Here we examined the limits of susceptibility of rivalry to predictive influences by asking whether binocular rivalry dynamics depend on multisensory congruence between abstract representations familiar to individuals with expertise in that domain of abstraction.…”
mentioning
confidence: 99%